2002
DOI: 10.1053/jhep.2002.34852
|View full text |Cite
|
Sign up to set email alerts
|

Methylation framework of cell cycle gene inhibitors in cirrhosis and associated hepatocellular carcinoma

Abstract: One of the main regulatory pathways reported to be altered in hepatocellular carcinoma (HCC) is that of cell cycle control involving RB1 gene-related cell inhibitors. We investigated p14 ARF , p15 INK4B M ethylation of normally unmethylated CpG islands is an alternative mechanism for loss of function of tumor suppressor genes in human cancer. p16 INK4A is one of the most important tumor suppressor genes belonging to the family of cell cycle inhibitors, encoding a protein that binds competitively to cyclin-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 16 publications
6
97
2
Order By: Relevance
“…RASSF1A, E-Cadherin and p16INK4A methylation As previously reported (Roncalli et al, 2002), 1 mg of genomic DNA in a volume of 50 ml was denatured by NaOH for 10 min at 371C; 30 ml of 10 mM hydroquinone (Sigma, Saint Louis, MO, USA) and 520 ml of 3 M sodium bisulphite (Sigma, Saint Louis, MO, USA) at pH 5, both freshly prepared, were added and mixed, and samples were incubated at 501C for 16 h. Modified DNA was purified using the Wizard DNA purification resin according to the manufacturer's instruction (Promega, Milano, Italy) and eluted into 50 ml of water. Modification was completed by NaOH treatment (final concentration 0.3 M) for 5 min at room temperature, followed by ethanol precipitation.…”
Section: P53 Mutationsupporting
confidence: 81%
See 1 more Smart Citation
“…RASSF1A, E-Cadherin and p16INK4A methylation As previously reported (Roncalli et al, 2002), 1 mg of genomic DNA in a volume of 50 ml was denatured by NaOH for 10 min at 371C; 30 ml of 10 mM hydroquinone (Sigma, Saint Louis, MO, USA) and 520 ml of 3 M sodium bisulphite (Sigma, Saint Louis, MO, USA) at pH 5, both freshly prepared, were added and mixed, and samples were incubated at 501C for 16 h. Modified DNA was purified using the Wizard DNA purification resin according to the manufacturer's instruction (Promega, Milano, Italy) and eluted into 50 ml of water. Modification was completed by NaOH treatment (final concentration 0.3 M) for 5 min at room temperature, followed by ethanol precipitation.…”
Section: P53 Mutationsupporting
confidence: 81%
“…One section from each tissue was stained with hematoxylin -eosin to distinguish neoplastic tissue from the nonmalignant counterpart. After manual dissection, DNA was extracted from the unstained section of the malignant tissue as described previously (Roncalli et al, 2002). Briefly, tissue sections were deparaffinised using 100% xylene (Sigma, Saint Louis, MO, USA) followed by 100% ethanol.…”
Section: Dna Extractionmentioning
confidence: 99%
“…Kaneto et al, using methylation specific PCR and immunohistochemistry, had detected methylation of p16 promoter in HCC (72.6%, 16/22) and loss of expression in all methylation positive HCC [13] . Roncalli et al reported that methylation of p16 promoter with complete loss of immunoreactivity occurred in 27 of 33 HCC (82%) [15] . Thus, our result, which was consistent with other reports, suggested that association of p16 gene 5'CpG island methylation with transcription inactivation might play an important role in hepatocarcinogenesis, and 5'CpG island methylation was the major mechanism of p16 gene inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al reported a high frequency of p15 methylation (64%, 15/25) in HCC. Yang et al showed methylation of p15 in 49% of HCC [14][15][16] . Based on Northern blot analysis, our study found that a complete loss of p15 mRNA expression accounted for a small portion of the p15 methylation positive cases, while the majority had decreased transcription level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation